Perceived barriers to the production of scientific articles among faculty members of some of Iranian dental schools - Ghasemi, Hadi; Harati, Mohammad; Mohebbi Rad, Masoud; Farahnaki, Arash; Hosseini Kordkheili, Seyyed Mohammadreza (Journal of Dental School, 2018)
Objectives To evaluate barriers for production of scientific dental articles by Iranian dental faculty members. Methods An anonymous self-administered questionnaire distributed among faculty members of all dental schools in Iran during June-December 2010. The respondents rated their level of agreement with eleven sentences regarding what they perceive as barriers on scientific dental article production based on a 5-point Likert scale. The data were analyzed using Chi-square test. Results Totally, 330 faculty members completed the questionnaires; >50% were men, and >40 year-olds. About three-fourth of the respondents were assistant professor. More than 80% of the respondents reported to have at least one published Persian article and >50% at least one published English article; older faculty members more than younger, and associate professors more than other academic ranks (p<0.01). “No access to an English editing center”, “insufficient skill for scientific writing in English”, “inappropriate condition for writing in dental school”, and “time limit due to high load of clinical work in dental school” were top four rated perceived barriers. Conclusion The concerns of faculty members for the production of scientific dental documents must be considered. Provision of proper time and condition for writing in the dental school, enhancement of their capacity for scientific writing and establishment of an English editing center in each university may facilitate scientific article production.